Secondary battery and electric device

By using high-tap density graphite material and high-content conductive agent in the negative electrode film layer of the secondary battery, the problem of insufficient cycle life of the secondary battery is solved, and the cycle stability and high-temperature storage performance of the battery are significantly improved.

CN119852537APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311679355.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing secondary batteries have insufficient cycle life during circulation, resulting in reduced battery performance and weakened battery life.

Method used

By using graphite material with high tap density in the negative electrode film layer and adding relatively high content of conductive agents therein, the electrical contact between graphite materials is improved, the generation of black spots is reduced, and the circulation stability of the battery is extended.

Benefits of technology

It effectively improves the cycle stability and storage performance of secondary batteries, especially under high temperature conditions, extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852537A_ABST
    Figure CN119852537A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and a power utilization device, the secondary battery comprises a negative electrode plate, the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, the negative electrode film layer comprises a negative electrode active material and a conductive agent, the negative electrode active material comprises a graphite material, the tap density of the graphite material is greater than or equal to 1.2 g / cm < 3 >; and based on the total mass of the negative electrode film layer, the mass ratio of the conductive agent is greater than or equal to 1.6%. The cycling stability of the secondary battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a secondary battery and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.

[0003] As the requirements for the endurance of electrical devices continue to increase, more stringent requirements are placed on the cycle life of secondary batteries. How to further improve the cycle life of secondary batteries is a technical problem that those skilled in the art need to solve urgently. Summary of the invention

[0004] The purpose of the present application is to provide a secondary battery and an electrical device, which can further improve the cycle stability of the secondary battery.

[0005] The present application provides a secondary battery in a first aspect, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material and a conductive agent, wherein the negative electrode active material comprises a graphite material, and the tap density of the graphite material is greater than or equal to 1.2 g / cm 3 ; and based on the total mass of the negative electrode film layer, the mass proportion of the conductive agent is greater than or equal to 1.6%.

[0006] By including a relatively high content of conductive agent in the negative electrode film layer containing a high tap density, the electrical contact between graphite materials can be effectively enhanced, the degree of black spots generated at the negative electrode can be reduced, the advantage of the high tap density graphite material in terms of high cycle life can be fully utilized, and the cycle stability of the battery can be improved.

[0007] In any embodiment of the present application, based on the total mass of the negative electrode film layer, the mass proportion of the conductive agent is 1.6%-2.5%, and can be optionally 1.65%-2.0%.

[0008] Conductive agents within a suitable range can enhance the electrical contact between graphite materials while enabling effective dispersion of the slurry. Excessive loss of lithium ions during storage due to excessive amounts of highly active conductive agents in the slurry will not occur, thereby reducing the probability of side reactions during the cycle and further improving the cycle stability, storage performance, and especially high-temperature storage performance of the secondary battery.

[0009] In any embodiment of the present application, the tap density of the graphite material is 1.20 g / cm 3 -1.42g / cm 3, optional 1.25g / cm 3 -1.35g / cm 3 .

[0010] A tap density within a suitable range can improve the cycle stability of the secondary battery while reducing the probability of black spots on the negative electrode sheet and improving the quality of the negative electrode sheet.

[0011] In any embodiment of the present application, the graphite material includes primary particles; optionally, based on the total number of particles of the graphite material, the number of primary particles in the graphite material accounts for greater than or equal to 85%.

[0012] Compared with secondary particles, primary particles can effectively reduce the grain boundary content, reduce the probability of side reactions between graphite materials and electrolytes, improve the uniformity of the electrodes, and further improve the cycle stability of secondary batteries.

[0013] In any embodiment of the present application, Dv1 of the graphite material is 1.0 μm-4.0 μm, and can be optionally 1.5 μm-3.0 μm.

[0014] The applicant found that the Dv1 particle size of the graphite material has an important influence on the electrochemical performance of the secondary battery. The graphite material has a Dv1 within a suitable range, which can not only make the negative electrode film layer have a certain proportion of fine powder, that is, small-particle graphite material, which is beneficial to improve the electrical contact of the negative electrode film layer, improve the dynamic performance, reduce the severity of the negative electrode black spots during battery recycling, and reduce the probability of "diving" in the electrochemical performance of the battery; it can also reduce the probability of small-particle graphite materials blocking the pores of the negative electrode film layer, maintain normal electrode pores so that the electrolyte has high wettability, reduce the risk of negative electrode lithium plating, and further improve the cycle stability of the battery.

[0015] In any embodiment of the present application, the volume distribution particle size Dv50 of the graphite material is 10 μm-18 μm, and can be optionally 12 μm-16 μm.

[0016] Graphite materials with Dv50 within the above range can easily form effective connections in the negative electrode film layer to improve the conductivity of active ions and electrons; they can also form a reasonable pore structure in the negative electrode film layer, thereby comprehensively improving the cycle stability of the secondary battery.

[0017] In any embodiment of the present application, the particle size distribution of the graphite material (Dv90-Dv10) / Dv50 is 1.20-1.70, and can be optionally 1.35-1.60.

[0018] The particle size distribution of the graphite material is within the above range, which is beneficial to reducing the bridging phenomenon between graphite materials and improving the electrical contact of the negative electrode film layer, and is also beneficial to improving the uniformity of the dispersion of the graphite material in the slurry, thereby comprehensively improving the cycle performance of the battery.

[0019] In any embodiment of the present application, the specific surface area of ​​the graphite material is 0.6 m 2 / g-1.5m 2 / g, optional 0.8m 2 / g-1.4m 2 / g.

[0020] Graphite materials having a specific surface area within the above range can reduce the consumption of active ions in the formation of the solid electrolyte membrane (SEI membrane), reduce the probability of side reactions, and improve the cycle stability of the battery.

[0021] In any embodiment of the present application, the oil absorption value of the graphite material is less than or equal to 45 ml / 100 g, and can be optionally 25 ml / 100 g-44 ml / 100 g.

[0022] The oil absorption value of graphite materials can reflect the dispersibility of graphite materials in negative electrode slurry to a certain extent. A large oil absorption value of graphite materials means that the graphite materials need to be infiltrated with more dispersants, such as sodium carboxymethyl cellulose, during the dispersion process, and the slurry is more likely to settle, resulting in unstable quality during the electrode coating process and uneven thickness of the electrode after cold pressing. Graphite materials with oil absorption values ​​within a suitable range have excellent dispersibility in negative electrode slurry, and the negative electrode slurry exhibits good anti-sedimentation and uniformity, making it easy to prepare electrodes of uniform quality, reducing the probability of local current density unevenness during charging and discharging, reducing lithium precipitation caused by polarization of the electrode, improving the cycle stability of the battery, and extending the service life of the battery.

[0023] In any embodiment of the present application, the graphitization degree of the graphite material is 88%-93%, and optionally 89%-92%.

[0024] The graphite material with a graphitization degree within the above range has a larger interlayer spacing, which is conducive to the rapid deintercalation of active ions, reduces the expansion rate of the graphite material during the cycle process, and further improves the long cycle life of the battery.

[0025] In any embodiment of the present application, the compaction density of the negative electrode film layer is 1.40 g / cm 3 -1.55g / cm 3 ; and / or, the surface density of the negative electrode film layer is 7 mg / cm 2 ~14mg / cm 2 .

[0026] In any embodiment of the present application, the graphite material is artificial graphite.

[0027] In any embodiment of the present application, the conductive agent includes at least one of conductive carbon black, acetylene black, graphite, graphene, carbon nanotubes, and carbon nanofibers.

[0028] A second aspect of the present application provides an electrical device, which includes the secondary battery of the first aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0030] Figure 1 It is a schematic diagram of one embodiment of the secondary battery of the present application.

[0031] Figure 2 It is an exploded schematic diagram of one embodiment of the secondary battery of the present application.

[0032] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.

[0033] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0034] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.

[0035] Figure 6 It is a schematic diagram of one embodiment of an electric device including the secondary battery of the present application as a power source.

[0036] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are explained as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 secondary battery, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION

[0037] Hereinafter, the embodiments of the secondary battery and the electric device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0038] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0039] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0040] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0041] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0042] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0043] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0044] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.

[0045] If not otherwise specified, the values ​​of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.

[0046] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.

[0047] In the present application, the terms "plurality" and "multiple" refer to two or more.

[0048] With the continuous development of the new energy industry, lithium battery energy storage systems have received more and more attention. Lithium battery energy storage system is a device that uses lithium batteries for energy storage. It can store energy generated by renewable energy sources such as solar photovoltaics and wind power, and can also be used as an auxiliary facility for the power grid. Compared with power batteries, energy storage batteries pay more attention to the cycle life of batteries. In order to pursue the long cycle life of batteries, R&D personnel usually choose negative electrode materials with high tap density, because the negative electrode materials with high tap density are subjected to less pressure during the cold pressing process of the pole piece, which is conducive to maintaining the integrity of the particles and reducing the low stress inside the particles, reducing the probability of side reactions while maintaining the long-period pore structure of the pole piece, ensuring the smooth lithium insertion path, reducing polarization, providing the battery with long cycle cycle kinetic performance, and improving the cycle life of the battery. However, the applicant found in the research and development process that after a long cycle, as the degree of charging deepens, the negative electrode interface is prone to serious black spot phenomenon, which causes local current unevenness and polarization, causing the battery to lose electrochemical activity, accelerate capacity decay, and cause the battery performance to "dive", and cannot give full play to the advantages of high cycle life of high tap density graphite materials.

[0049] Based on this, the present application provides a secondary battery, comprising a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, the negative electrode film layer comprising a negative electrode active material and a conductive agent, the negative electrode active material comprising a graphite material, and the tap density of the graphite material is greater than or equal to 1.2 g / cm 3; and based on the total mass of the negative electrode film layer, the mass proportion of the conductive agent is greater than or equal to 1.6%.

[0050] As used herein, the term "tapped density" refers to the mass per unit volume of powder in a container measured after being tapped under specified conditions.

[0051] In the present application, the tap density of the graphite material can be tested by a method known in the art. As an example, GB / T 5162-2006 can be referred to and the tap density of the graphite material can be measured by a powder tap density tester. The test instrument can be Dandong Better BT-301, and the test parameters are as follows: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, vibration number 5000 times, and measuring cylinder 25mL.

[0052] In some embodiments, the tap density of the graphite material is 1.2 g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 , 1.35g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3 , 1.5g / cm 3 Or any range of values ​​in between.

[0053] In some embodiments, based on the total mass of the negative electrode film layer, the mass proportion of the conductive agent is 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0% or any numerical range therebetween.

[0054] During the formation stage of secondary batteries, the negative electrode active material and the electrolyte will undergo an electrochemical reaction to generate a solid electrolyte interface (SEI), accompanied by the generation of gas. In this process, some negative electrode active material particles have poor electrical contact with the surrounding particles and cannot form a complete SEI film in time, resulting in a lag in the formation of the SEI film and gas production. The gas generated by this lag cannot be discharged in time with the formation process and is retained between the negative electrode plate and the separator, hindering the charging process of active ions escaping from the positive electrode, passing through the separator, and embedding into the negative electrode, which may cause black spot defects on the negative electrode plate.

[0055] The researchers found that the reason why serious black spots appeared on the negative electrode was that the graphite material with high tap density was easy to form a dense stack, and the electrode could achieve the expected compaction density under a lower cold pressing pressure; however, the lower cold pressing pressure made it impossible for the negative electrode material and the conductive agent to form a close electrical contact during the compaction process, which increased the probability of black spots.

[0056] By including a relatively high content of conductive agent in the negative electrode film layer containing a high tap density, the electrical contact between graphite materials can be effectively enhanced, the degree of black spots generated at the negative electrode can be reduced, the probability of black spots generated at the negative electrode can be reduced, the advantage of high tap density graphite materials in terms of high cycle life can be fully utilized, and the cycle stability of the battery can be improved.

[0057] In some embodiments, based on the total mass of the negative electrode film layer, the mass proportion of the conductive agent is 1.6%-2.5%, and can be 1.65%-2.0%.

[0058] Conductive agents within a suitable range can enhance the electrical contact between graphite materials while enabling effective dispersion of the slurry. Excessive loss of lithium ions during storage due to excessive amounts of highly active conductive agents in the slurry will not occur, thereby reducing the probability of side reactions during the cycle and further improving the cycle stability, storage performance, and especially high-temperature storage performance of the secondary battery.

[0059] In some embodiments, the tap density of the graphite material is 1.20 g / cm 3 -1.42g / cm 3 , optional 1.25g / cm 3 -1.35g / cm 3 .

[0060] A tap density within a suitable range can improve the cycle stability of the secondary battery while reducing the probability of black spots on the negative electrode sheet and improving the quality of the negative electrode sheet.

[0061] In some embodiments, the graphite material includes primary particles; optionally, based on the total number of particles of the graphite material, the number of primary particles in the graphite material accounts for greater than or equal to 85%.

[0062] As used herein, the term "primary particles" refers to particles in a non-agglomerated state.

[0063] In the present application, the percentage of primary particles in the graphite material can be tested by methods known in the art. As an example, a test sample is randomly selected in the negative electrode film layer, and multiple test areas are randomly selected in the test sample. Images of the multiple test areas are obtained using a scanning electron microscope. The ratio of the number of graphite material particles with primary particle morphology in each image to the total number of graphite material particles is counted, and the average value of the multiple statistical results is the percentage of primary particles in the graphite material.

[0064] In some embodiments, based on the total number of particles of the graphite material, the number of primary particles in the graphite material accounts for 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100% or any range therebetween.

[0065] Compared with agglomerated secondary particles, primary particles can effectively reduce the grain boundary content, reduce the probability of side reactions between graphite materials and electrolytes, improve the uniformity of the electrodes, and further improve the cycle stability of secondary batteries.

[0066] In some embodiments, Dv1 of the graphite material is 1.0 μm-4.0 μm, and optionally 1.5 μm-3.0 μm.

[0067] The volume distribution particle size Dv1 of the graphite negative electrode active material has a well-known meaning in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 1%.

[0068] In the present application, the volume distribution particle size Dv1 of the graphite material can be tested by a method known in the art. As an example, referring to GB / T 19077-2016, it is measured by a laser particle size analyzer. The testing instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0069] In some embodiments, the Dv1 of the graphite material is 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 3.5 μm, 4.0 μm or any range therebetween.

[0070] The applicant found that the Dv1 particle size of the graphite material has an important influence on the electrochemical performance of the secondary battery. The graphite material has a Dv1 within a suitable range, which can not only make the negative electrode film layer have a certain proportion of fine powder, that is, small-particle graphite material, which is beneficial to improve the electrical contact of the negative electrode film layer, improve the dynamic performance, reduce the severity of the negative electrode black spots during battery recycling, and reduce the probability of "diving" in the electrochemical performance of the battery; it can also reduce the probability of small-particle graphite materials blocking the pores of the negative electrode film layer, maintain normal electrode pores so that the electrolyte has high wettability, reduce the risk of negative electrode lithium plating, and further improve the cycle stability of the battery.

[0071] In some embodiments, the Dv50 of the graphite material is 10 μm-18 μm, and optionally 12 μm-16 μm.

[0072] In some embodiments, the Dv50 of the graphite material is 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 m, 16 m, 17 m, 18 m, or any range therebetween.

[0073] Graphite materials with Dv50 within the above range can easily form effective connections in the negative electrode film layer to improve the conductivity of active ions and electrons; they can also form a reasonable pore structure in the negative electrode film layer, thereby comprehensively improving the cycle stability of the secondary battery.

[0074] In some embodiments, the particle size distribution of the graphite material (Dv90-Dv10) / Dv50 is 1.20-1.70, and can be optionally 1.35-1.60.

[0075] As used herein, the term "particle size distribution" refers to a measure of the breadth of the distribution of particle sizes.

[0076] In some embodiments, the particle size distribution of the graphite material (Dv90-Dv10) / Dv50 is 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.65, 1.70 or any range therebetween.

[0077] The particle size distribution of the graphite material is within the above range, which is beneficial to reducing the bridging phenomenon between graphite materials and improving the electrical contact of the negative electrode film layer, and is also beneficial to improving the uniformity of the dispersion of the graphite material in the slurry, thereby comprehensively improving the cycle performance of the battery.

[0078] In some embodiments, the specific surface area of ​​the graphite material is 0.6 m 2 / g-1.5m 2 / g, optional 0.8m 2 / g-1.4m 2 / g.

[0079] In the present application, the specific surface area of ​​the graphite material can be tested by methods known in the art. As an example, referring to GB / T 19587-2017, the specific surface area analysis test method of nitrogen adsorption is used for testing, and the specific surface area is calculated by the BET (BrunauerEmmett Teller) method. The testing instrument can be the Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.

[0080] In some embodiments, the specific surface area of ​​the graphite material is 0.6 m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g or any range of values ​​between them.

[0081] Graphite materials having a specific surface area within the above range can reduce the consumption of active ions in the formation of the solid electrolyte membrane (SEI membrane), reduce the probability of side reactions, and improve the cycle stability of the battery.

[0082] In some embodiments, the oil absorption value of the graphite material is less than or equal to 45 ml / 100 g, and can be optionally 25 ml / 100 g-44 ml / 100 g.

[0083] In this document, the term "oil absorption value" refers to the volume of linseed oil that can be absorbed by 100g of graphite material. For example, if the oil absorption value of a graphite material is 40ml / 100g, it means that 100g of the graphite material can absorb 40ml of linseed oil.

[0084] The oil absorption value of graphite material can be tested by methods and equipment known in the art, as shown below: obtain test oil and graphite material samples respectively, and set the torque threshold of the oil absorption value tester; add oil to the sample in the mixing chamber of the oil absorption value tester at a constant speed, and as the oil absorption of the sample increases, the viscosity of the mixture of the sample and the oil continues to increase. When the viscosity of the mixture reaches the preset torque threshold of the oil absorption value tester, stop and calculate the volume of oil absorbed by the sample per unit mass, which is the oil absorption value QI of the sample. The test oil is linseed oil (DBP), and the torque threshold is 1N.

[0085] In some embodiments, the oil absorption value of the graphite material may be 35 ml / 100 g, 36 ml / 100 g, 37 ml / 100 g, 38 ml / 100 g, 39 ml / 100 g, 40 ml / 100 g, 41 ml / 100 g, 42 ml / 100 g, 43 ml / 100 g, 44 ml / 100 g, 45 ml / 100 g or any range therebetween.

[0086] The oil absorption value of graphite materials can reflect the dispersibility of graphite materials in negative electrode slurry to a certain extent. A large oil absorption value of graphite materials means that the graphite materials need to be infiltrated with more dispersants, such as sodium carboxymethyl cellulose, during the dispersion process, and the slurry is more likely to settle, resulting in unstable quality during the electrode coating process and uneven thickness of the electrode after cold pressing. Graphite materials with oil absorption values ​​within a suitable range have excellent dispersibility in negative electrode slurry, and the negative electrode slurry exhibits good anti-sedimentation and uniformity, making it easy to prepare electrodes of uniform quality, reducing the probability of local current density unevenness during charging and discharging, reducing lithium precipitation caused by polarization of the electrode, improving the cycle stability of the battery, and extending the service life of the battery.

[0087] In some embodiments, the graphite material has a degree of graphitization of 88%-93%, and optionally 89%-92%.

[0088] As used herein, the term "degree of graphitization" refers to an index measuring the degree to which carbon atoms form a close-packed hexagonal graphite crystal structure.

[0089] In the present application, the graphitization degree of the graphite material can be tested by methods known in the art. As an example, an X-ray diffractometer (such as Bruker D8 Discover) is used for testing, and JIS K0131-1996 and JB / T4220-2011 are referred to to obtain the average interlayer spacing d002 of the (002) crystal plane in the crystal structure of the graphite material, and then the graphitization degree is calculated according to the formula g=(0.344-d002) / (0.344-0.3354)×100%. In the above formula, d002 is the average interlayer spacing of the (002) crystal plane in the crystal structure of the graphite material expressed in nanometers (nm).

[0090] In some embodiments, the graphite material has a degree of graphitization of 88%, 89%, 90%, 91%, 92%, 93% or any range therebetween.

[0091] The graphite material with a graphitization degree within the above range has a larger interlayer spacing, which is conducive to the rapid deintercalation of active ions, reduces the expansion rate of the graphite material during the cycle process, and further improves the long cycle life of the battery.

[0092] In some embodiments, the compaction density of the negative electrode film layer is 1.40 g / cm 3 -1.55g / cm 3 ; and / or, the surface density of the negative electrode film layer is 7 mg / cm 2 ~14mg / cm 2 .

[0093] In the present application, the compaction density of the negative electrode film layer can be tested by methods known in the art. As an example, an electronic balance is used to weigh a negative electrode sheet test sample with an area of ​​S, and the weight is recorded as W1, and a micrometer is used to measure the thickness T1 of the negative electrode sheet. Then the negative electrode film of the weighed negative electrode sheet is wiped off, the weight of the negative electrode current collector is weighed, recorded as W2, and the thickness T2 of the negative electrode current collector is measured using a micrometer. Then the compaction density of the negative electrode film layer PD = (W1-W2) / [(T1-T2)×S]

[0094] In some embodiments, the compaction density of the negative electrode film layer is 1.40 g / cm 3 , 1.43g / cm 3 , 1.46g / cm 3 , 1.49g / cm 3 , 1.52g / cm 3 , 1.55g / cm 3 Or any range of values ​​in between.

[0095] In the present application, the surface density of the negative electrode film layer can be tested by a method known in the art. As an example, a cold-pressed negative electrode sheet is punched into a small disc with an area of ​​S1, and its weight is weighed and recorded as M1. Then the negative electrode film of the weighed negative electrode sheet is wiped off, and the weight of the negative electrode current collector is weighed and recorded as M0. The surface density of the negative electrode film = (the weight of the negative electrode sheet M1-the weight of the negative electrode current collector M0) / S1.

[0096] In some embodiments, the surface density of the negative electrode film layer is 7 mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 、10mg / cm 2 、11mg / cm 2 , 12mg / cm 2 、13mg / cm 2 、14mg / cm 2 Or any range of values ​​in between.

[0097] In some embodiments, the graphite material is artificial graphite.

[0098] In some embodiments, the conductive agent includes at least one of conductive carbon black, acetylene black, graphite, graphene, carbon nanotubes, and carbon nanofibers.

[0099] In some embodiments, the method for preparing the graphite material includes the following steps: providing raw materials, the raw materials including at least one of petroleum coke, needle coke, and asphalt coke, and based on the total volume of the raw material structure, the volume of the mosaic type organizational structure and the regional type organizational structure in the raw material accounts for not less than 60%; processing the raw materials to obtain a precursor; and graphitizing the precursor to obtain the graphite material.

[0100] In this article, the term "petroleum coke" refers to the coke formed by high-temperature carbonization of petroleum residue or petroleum asphalt, which is called petroleum coke.

[0101] In this article, the term "needle coke" refers to coal tar pitch or petroleum pitch, which can generate coke with a needle-like texture after being carbonized in the liquid phase to generate an anisotropic intermediate phase and then subjected to processes such as high-temperature carbonization. This is called needle coke.

[0102] As used herein, the term "pitch coke" refers to a solid material produced by carbonizing coal tar pitch at high temperatures.

[0103] The above-mentioned raw materials usually include at least one of mosaic, regional and fiber structures. Usually, based on the morphological characteristics and isochromatic zone size of the coke material under a polarizing microscope, isochromatic zone microstructures with a size less than 30 μm are judged as mosaic, isochromatic zone microstructures with a size greater than 30 μm are judged as regional, and anisotropic strip-shaped isochromatic zones are judged as fiber structures.

[0104] In this application, the proportion of mosaic structure and regional structure in the raw material can be tested by methods known in the art. As an example, take the raw material according to GB 1997-89, mix the raw material crushed to 1mm, shrink it to 40g~50g, use a square hole sieve to take 0.07mm~1.0mm grade sample 4g~5g for film making; prepare powder coke and block coke light film according to MT 116.1-86, the diameter of the powder coke light film shall not be less than 22mm, and the volume occupied by the cement shall be less than 1 / 3; place the sample on a slide with cement, flatten it, and place it on the stage to align the focus, calibrate the microscope, and adjust the polarizer and analyzer to make them orthogonal. Insert the azurite inspection plate (1λ) to make the field of view present the interference color of primary red; determine the step length of the moving ruler to ensure that more than 400 effective measuring points are evenly distributed, and the point spacing is 0.3~0.5mm and the line spacing is generally 0.5~0.8mm. Starting from one end of the sample, determine the type of microstructure under the intersection of the crosshairs, and divide the number of effective measuring points of the mosaic-type structure and regional-type structure optical organization by the total number of statistical testing points as the volume content of the mosaic-type structure and regional-type structure in the raw material.

[0105] In some embodiments, based on the total volume of the raw material structure, the volume proportion of the mosaic structure and the regional structure in the raw material is 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100% or any numerical range therebetween.

[0106] In this article, the term "graphitization treatment" refers to the heat treatment process of graphite materials. Under high temperature, the graphite material transforms from a two-dimensional carbon network structure to a three-dimensional ordered structure through "microcrystal" growth.

[0107] In some embodiments, the power of the graphitization process is 70% to 90% of the rated power of the equipment.

[0108] In some embodiments, the power of the graphitization treatment can be selected as 70%, 75%, 80%, 85%, 90% of the rated power of the equipment, or any range of values ​​therebetween. It is understood that the graphitization treatment equipment refers to any device capable of graphitization treatment, including but not limited to Acheson furnace, box furnace, inner series furnace, continuous graphitization, electric calcining furnace, medium frequency furnace, tubular furnace and other devices. Among them, the rated power of graphitization treatment equipment produced by different manufacturers may be different, and it can be selected according to the actual situation.

[0109] In some embodiments, the graphitization treatment equipment is an inner series furnace, and the rated power of the inner series furnace is 25000-32000W.

[0110] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the rated power of the Acheson furnace is 28000-30000W.

[0111] In some embodiments, the maximum power of the graphitization treatment is 23000 W-25000 W. For example, it can be 23000 W, 23500 W, 24000 W, 24500 W, 25000 W, or any range therebetween.

[0112] In some embodiments, the graphitization treatment is performed at a constant power time of 10 h to 50 h at the maximum power.

[0113] In some embodiments, the graphitization treatment is performed at a constant power time of maximum power of 10 h, 13 h, 16 h, 19 h, 22 h, 25 h, 28 h, 31 h, 33 h, 36 h, 39 h, 42 h, 45 h, 48 h, 50 h, or any range therebetween.

[0114] In some embodiments, the graphitization treatment equipment is an internal series furnace, and the graphitization treatment is performed at a constant power time of maximum power for 10 hours to 30 hours.

[0115] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the graphitization treatment is performed at a constant power time of maximum power for 30 hours to 50 hours.

[0116] In some embodiments, the temperature of the graphitization treatment is 2800°C to 3000°C.

[0117] In some embodiments, the temperature of the graphitization treatment is 2800° C., 2900° C., 3000° C., or any range therebetween.

[0118] By controlling the proportion of the embedded and regional structure areas in the raw materials within an appropriate range, on the one hand, graphite materials with low graphitization degree and low powder compaction density can be obtained, which is beneficial to improving the cycle performance of the battery. On the other hand, graphite materials with high gram capacity and tap density can also be obtained, thereby improving the energy density of the battery.

[0119] In some embodiments, the processing of raw materials to obtain a precursor specifically includes the following steps: crushing, shaping and grading the raw materials to obtain secondary raw materials; removing part of the fine powder in the secondary raw materials, wherein the removed fine powder accounts for 18%-45% of the total mass of the secondary raw materials, to obtain a precursor, wherein the Dv50 of the fine powder is 3μm-7μm, and Dv99 is less than or equal to 30μm.

[0120] Crushing is the process of reducing the particle size of the raw material, and the raw material can be crushed by any mechanical device such as a crusher, a mechanical mill, etc. In some embodiments, the raw material is crushed to a set particle size before being screened.

[0121] The shaping treatment can reduce the burrs on the surface of the crushed raw materials, which is conducive to obtaining graphite materials with high sphericity.

[0122] Classification is the process of adjusting the particle size distribution of the raw materials to obtain the first precursor that meets the particle size requirements. The particle size and particle size distribution of the precursor can be controlled by adjusting the classification frequency and air intake. Classification can reduce the content of large and small particles in the precursor.

[0123] In some embodiments, removing some fine powder in the secondary raw material to adjust the Dv1 of the graphite material is beneficial to making the Dv1 of the graphite material within a suitable range so that the graphite material can easily form a good electrical contact in the negative electrode film layer.

[0124] In some embodiments, the volume distribution particle size Dv50 of the precursor is 12 μm-18 μm.

[0125] In some embodiments, the volume distribution particle size Dv50 of the precursor can be selected as 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm or any numerical range therebetween.

[0126] In some embodiments, the particle size distribution of the precursor (Dv90-Dv10) / Dv50 is 1.3-2.0.

[0127] In some embodiments, the particle size distribution of the precursor (Dv90-Dv10) / Dv50 can be selected as 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0.

[0128] Controlling the volume distribution particle size Dv50 or (Dv90-Dv10) / Dv50 of the precursor within a suitable range helps to prepare graphite materials with a volume distribution particle size Dv50 or (Dv90-Dv10) / Dv50 within a suitable range, which can improve the cycle performance of the battery.

[0129] The present application has no particular restrictions on the type of secondary battery. For example, the secondary battery can be a lithium-ion battery, etc. In general, a secondary battery includes a positive electrode plate, a negative electrode plate, and an electrolyte, etc. During the charge and discharge process of the secondary battery, active ions are embedded and removed back and forth between the positive electrode plate and the negative electrode plate, and the electrolyte plays a role in conducting active ions between the positive electrode plate and the negative electrode plate. The present application has no particular restrictions on the type of the electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (ie, an electrolyte). Secondary batteries using electrolytes and some secondary batteries using solid electrolytes may also include a separator, which is arranged between the positive electrode plate and the negative electrode plate to play an isolation role.

[0130] [Negative electrode]

[0131] In some embodiments, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0132] In some embodiments, the negative electrode film layer may further include other negative electrode active materials in addition to the above-mentioned graphite materials. In some embodiments, the other negative electrode active materials include but are not limited to one or more of conventional natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide and tin alloy material.

[0133] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0134] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.

[0135] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0136] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0137] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the present application also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode collector and the negative electrode film layer and disposed on the surface of the negative electrode collector; in some embodiments, the negative electrode plate described in the present application also includes a protective layer covering the surface of the negative electrode film layer.

[0138] [Positive electrode]

[0139] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0140] The positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0141] The positive electrode film layer generally comprises a positive electrode active material, an optional binder and an optional conductive agent. The positive electrode film layer is generally formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is generally formed by dispersing the positive electrode active material, the optional conductive agent, the optional binder and any other components in a solvent and stirring evenly. The solvent may be N-methylpyrrolidone (NMP), but is not limited thereto. As an example, the binder for the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. As an example, the conductive agent for the positive electrode film layer includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0142] The positive electrode active material may be a positive electrode active material for a secondary battery known in the art.

[0143] When the secondary battery of the present application is a lithium-ion battery, the positive electrode active material may include, but is not limited to, one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds. Examples of the lithium transition metal oxide may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the lithium-containing phosphate may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.

[0144] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion battery may include a general formula of Li a Nib Co c M d O e A f One or more of lithium transition metal oxides and their modified compounds of. 0.8 ≤ a ≤ 1.2, 0.5 ≤ b < 1, 0 < c < 1, 0 < d < 1, 1 ≤ e ≤ 2, 0 ≤ f ≤ 1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A is selected from one or more of N, F, S, and Cl.

[0145] In some embodiments, by way of example, the positive electrode active material for a lithium-ion battery may include LiCoO 2 , LiNiO 2 , LiMnO 2 , LiMn 2 O 4 , LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811), LiNi 0.85 Co 0.15 Al 0.05 O 2 , LiFePO 4 and LiMnPO 4 One or more of.

[0146] In the present application, the modified compounds of the above positive electrode active materials may be doping modification and / or surface coating modification of the positive electrode active materials.

[0147] [Electrolyte]

[0148] In some embodiments, the electrolyte uses an electrolytic solution, and the electrolytic solution includes an electrolyte salt and a solvent.

[0149] The type of the electrolyte salt is not specifically limited and can be selected according to actual needs.

[0150] When the secondary battery of the present application is a lithium ion battery, the electrolyte salt may include lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2 ), one or more of lithium difluorobis(oxalate) phosphate (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP).

[0151] The type of the solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent may include ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE) One or more.

[0152] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain properties of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high temperature performance of the secondary battery, and additives that improve the low temperature power performance of the secondary battery.

[0153] [Isolation film]

[0154] The present application has no particular limitation on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.

[0155] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.

[0156] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly by a winding process or a lamination process.

[0157] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0158] In some embodiments, the outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0159] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0160] In some embodiments, Figure 2 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.

[0161] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the secondary battery is obtained through vacuum packaging, standing, forming, shaping and other processes.

[0162] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.

[0163] Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3As shown, in the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0164] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0165] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0166] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0167] Electrical devices

[0168] The present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack of the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0169] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0170] Figure 6 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.

[0171] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0172] Example

[0173] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0174] Material 1

[0175] The petroleum coke with mosaic and regional structures accounting for 63.1% is crushed; the crushed material is shaped to obtain secondary raw materials, and fine powder accounting for 18% by mass of the secondary raw materials is removed. The remaining material is called precursor, and the obtained precursor has a Dv50 particle size of 15.5μm and a particle size distribution of (Dv90-Dv10) / Dv50 of 1.97; fine powder refers to components with Dv50 of 3μm-7μm and Dv99 less than or equal to 30μm.

[0176] The precursor was graphitized in an Acheson furnace (the rated power of the Acheson furnace was 30,000 W), the graphitization temperature was 2,800°C, the maximum power of the graphitization was 24,000 W, and after maintaining the maximum power for 40 hours, the surface temperature of the Acheson furnace crucible was cooled to 400°C, the graphite crucible was taken out, and the graphite material was obtained after screening and demagnetization.

[0177] The tap density of graphite material is 1.22g / cm 3 , Dv1 is 1.8μm, Dv50 is 14.6μm, particle size distribution (Dv90-Dv10) / Dv50 is 1.42, and specific surface area is 1.14m 2 / g, and the degree of graphitization is 91.1%.

[0178] Materials 2-5

[0179] The preparation method of material 2-5 is similar to that of material 1, except that the mass ratio of fine powder removed from the secondary raw material is adjusted. Detailed parameters are shown in Table 1.

[0180] Table 1

[0181]

[0182] Example 1

[0183] Preparation of secondary batteries

[0184] The prepared material 1, conductive agent carbon black (Super P), binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose were mixed in an appropriate amount of solvent deionized water at a weight ratio of 95.4:1.8:1.0:1.8 to form a negative electrode slurry. The negative electrode slurry was coated on both surfaces of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet was obtained. The compaction density of the negative electrode film layer was 1.48 g / cm 3 , surface density is 9.4mg / cm 2 .

[0185] The positive electrode active material lithium iron phosphate (LFP), the conductive agent Super P, and the binder PVDF were mixed in a mass ratio of 97:1:2, and the solvent N-methylpyrrolidone NMP was added. The system was stirred under the action of a vacuum mixer until it was uniform to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet was obtained after drying, cold pressing, and slitting. The compaction density of the positive electrode film layer is 2.50g / cm 3 , surface density is 20mg / cm 2 .

[0186] In an argon atmosphere glove box with a water content of <10ppm, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L, and then vinylene carbonate (VC) is added, and the content of VC is 2% of the total mass of the electrolyte.

[0187] Polypropylene film is used as the isolation film.

[0188] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0189] Examples 2-7 and Comparative Examples 1-2

[0190] The preparation method of the secondary battery is similar to that of Example 1, except that different graphite materials are used or the content of the conductive agent is adjusted, as shown in Table 2 for details.

[0191] Performance Testing

[0192] (1) Formation-End State of Charge (SOC) Test

[0193] At 25° C., the liquid-filled batteries prepared in the examples and comparative examples were charged at 0.33C, and the gas generated during the formation process was collected. When the total amount of gas did not increase, the corresponding SOC was recorded.

[0194] (2) Dark spot test

[0195] At 25°C, the batteries of the above embodiments and comparative examples were charged at a constant current of 0.33C to a voltage of 3.65V, and were disassembled in a drying room to observe whether there were black spots on the surface of the negative electrode plate; the total area of ​​black spots / total area of ​​the negative electrode plate ≤1%, and the area of ​​black spots in a single electrode plate / area of ​​a single electrode plate ≤8% were defined as primary black spots; 1% <total area of ​​black spots / total area of ​​the negative electrode plate ≤3%, or 8% <area of ​​black spots in a single electrode plate / area of ​​a single electrode plate ≤15% were defined as secondary black spots; the total area of ​​black spots / total area of ​​the negative electrode plate >3%, or the area of ​​black spots in a single electrode plate / area of ​​a single electrode plate >15%, were defined as tertiary black spots.

[0196] (3) Cycle performance test of secondary batteries

[0197] At 25°C, the batteries of the above embodiments and comparative examples were charged at 1C constant current to a voltage of 3.65V, then charged at 3.65V constant voltage to a current ≤ 0.05C, and then discharged at 1C constant current to a voltage of 2.5V. This was a charge and discharge process, and the discharge capacity C1 of the first cycle was recorded. The charge and discharge cycles were repeated until the battery capacity decayed to 70% of the initial capacity C1, and the number of cycles was recorded.

[0198] Test Results

[0199] The batteries of the embodiments and comparative examples were prepared according to the above method, and various performance parameters were measured. The results are shown in the table below.

[0200] Table 2

[0201]

[0202]

[0203] As can be seen from Examples 1-7 in Table 2, the secondary battery includes a negative electrode plate, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer includes a negative electrode active material and a conductive agent, the negative electrode active material includes a graphite material, and the tap density of the graphite material is greater than or equal to 1.2 g / cm 3; and the negative electrode film layer includes a conductive agent. When the mass proportion of the conductive agent is greater than or equal to 1.6% based on the total mass of the negative electrode film layer, the secondary battery can reduce the severity of black spots formed by high tap density graphite materials at the negative electrode, reduce the probability of battery performance "diving", and improve the battery's cycle stability.

[0204] As can be seen from Examples 1-4, when the Dv1 of the graphite material is 1.5 μm-3.0 μm, the formation SOC of the battery is further reduced and the cycle stability is further improved. Formation is the process of charging the battery for the first time and activating the electrochemical reaction inside the battery. As the formation charge proceeds, lithium ions are deintercalated from the positive electrode material, transported through the diaphragm to the negative electrode by the electrolyte and embedded in the negative electrode material, thereby forming a potential difference between the positive and negative electrodes, converting electrical energy into the chemical energy of the battery. When the formation voltage reaches a certain value, an oxidation-reduction reaction occurs at the solid-liquid interface of the negative electrode and the electrolyte to generate a solid electrolyte interface film (SEI film). The higher the formation SOC, the higher the amount of electricity charged during the formation process, the more lithium ions consumed to form the SEI film, the lower the first efficiency of the battery, and the greater the severity of black spots generated at the negative electrode of the battery. Reducing the formation SOC of the battery is conducive to reducing the severity of the negative electrode black spots and improving the cycle stability of the battery.

[0205] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A secondary battery, characterized in that: The invention comprises a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material and a conductive agent, wherein the negative electrode active material comprises a graphite material, and the tap density of the graphite material is greater than or equal to 1.2 g / cm 3 ; and based on the total mass of the negative electrode film layer, the mass proportion of the conductive agent is greater than or equal to 1.6%.

2. The secondary battery according to claim 1, characterized in that: Based on the total mass of the negative electrode film layer, the mass proportion of the conductive agent is 1.6%-2.5%, and can be optionally 1.65%-2.0%.

3. The secondary battery according to claim 1 or 2, characterized in that: The tap density of the graphite material is 1.20 g / cm 3 -1.42g / cm 3 , optional 1.25g / cm 3 -1.35g / cm 3 .

4. The secondary battery according to any one of claims 1 to 3, characterized in that: The graphite material includes primary particles; optionally, based on the total number of particles of the graphite material, the number of primary particles in the graphite material accounts for greater than or equal to 85%.

5. The secondary battery according to any one of claims 1 to 4, characterized in that: The Dv1 of the graphite material is 1.0 μm-4.0 μm, and can be optionally 1.5 μm-3.0 μm.

6. The secondary battery according to any one of claims 1 to 5, characterized in that: The volume distribution particle size Dv50 of the graphite material is 10 μm-18 μm, and can be optionally 12 μm-16 μm.

7. The secondary battery according to any one of claims 1 to 6, characterized in that: The particle size distribution of the graphite material (Dv90-Dv10) / Dv50 is 1.20-1.70, and can be optionally 1.35-1.

60.

8. The secondary battery according to any one of claims 1 to 7, characterized in that: The specific surface area of ​​the graphite material is 0.6 m 2 / g-1.5m 2 / g, optional 0.8m 2 / g-1.4m 2 / g.

9. The secondary battery according to any one of claims 1 to 8, characterized in that: The oil absorption value of the graphite material is less than or equal to 45 ml / 100 g, and can be optionally 25 ml / 100 g-44 ml / 100 g.

10. The secondary battery according to any one of claims 1 to 9, characterized in that: The graphitization degree of the graphite material is 88%-93%, and can be optionally 89%-92%.

11. The secondary battery according to any one of claims 1 to 10, characterized in that: The compaction density of the negative electrode film layer is 1.40 g / cm 3 -1.55g / cm 3 and / or, The surface density of the negative electrode film layer is 7 mg / cm 2 ~14mg / cm 2 .

12. The secondary battery according to any one of claims 1 to 11, characterized in that: The graphite material is artificial graphite.

13. The secondary battery according to any one of claims 1 to 12, characterized in that: The conductive agent includes at least one of conductive carbon black, acetylene black, graphite, graphene, carbon nanotubes, and carbon nanofibers.

14. An electrical device comprising the secondary battery according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Manufacturing method for High temperature lithium ion battery used in unmanned plane

    CN106784855A

  • Low-temperature lithium-ion battery

    CN109888368A

  • Secondary battery and method for preparing same, and device including secondary battery

    CN113875047A

  • Secondary battery and method for preparing same, and device including secondary battery

    CN113875050A

  • Artificial graphite and preparation method thereof, and secondary battery and electric device containing artificial graphite

    CN116745956A

Cited By

  • Secondary battery and electric device

    EP4800753A1